2008
DOI: 10.1016/j.ijpharm.2007.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric micelles for the solubilization and delivery of STAT3 inhibitor cucurbitacins in solid tumors

Abstract: Poly(ethylene oxide)-block-poly(ε-caprolactone) (PEO-b-PCL) and newly developed poly(ethylene oxide)-block-poly(α-benzyl carboxylate ε-caprolactone) (PEO-b-PBCL) micelles were evaluated for the solubilization and delivery of cucurbitacin I and B, poorly water soluble inhibitors of signal transducer and activator of transcription 3 (STAT3). Encapsulation of cucurbitacins in PEO-b-PCL and PEO-b-PBCL by co-solvent evaporation technique resulted in polymeric micelles <90 nm in diameter. The aqueous solubility of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…We inhibited ERK 1/2 phosphorylation with SL327, a selective inhibitor of MEK 1/2, the upstream MAPKK, [17][18][19][20] and STAT-3 phosphorylation with cucurbitacin E and I, compounds that target upstream Janus kinases. [21][22][23][24] We first assessed whether inhibiting ERK 1/2 phosphorylation with SL327 could attenuate the proliferation of normal B6 splenic T cells in response to anti-CD3 ϩ CD28 stimulation in vitro, and found a dose-dependent suppression of proliferation ( Figure 2A). We evaluated the toxicity of SL327 and found that T cells were not significantly apoptotic at concentrations below 100 ng/mL (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We inhibited ERK 1/2 phosphorylation with SL327, a selective inhibitor of MEK 1/2, the upstream MAPKK, [17][18][19][20] and STAT-3 phosphorylation with cucurbitacin E and I, compounds that target upstream Janus kinases. [21][22][23][24] We first assessed whether inhibiting ERK 1/2 phosphorylation with SL327 could attenuate the proliferation of normal B6 splenic T cells in response to anti-CD3 ϩ CD28 stimulation in vitro, and found a dose-dependent suppression of proliferation ( Figure 2A). We evaluated the toxicity of SL327 and found that T cells were not significantly apoptotic at concentrations below 100 ng/mL (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[7,9] Nanocarriers formed from self assembly of MePEO-b-PCL bearing pendent benzyl groups on their PCL block have particularly shown superior capacity for the encapsulation and controlling the release of hydrophobic drugs containing aromatic as well as hydrogen bond forming groups in their structure. [29] A new member in this family of block copolymers, i.e., MePEO-b-PCL copolymers bearing aliphatic stearyl side groups on the PCL block were synthesized (Scheme 1) and their potential in the solubilization of an aliphatic and amphiphilic drug, AmB, was assessed here. A similar strategy has proven to be successful in the solubilization and controlling the delivery of AmB from MePEO-b-poly(L-aspartic acid) based micellar carriers.…”
Section: Discussionmentioning
confidence: 99%
“…41 Inhibition of JAK2/STAT3 signaling with cucurbitacin-I (JSI-124), 42 a natural plant product, has been shown to have potent anti-cancer activities in hematological malignancies and solid tumors. [43][44][45][46][47] Several lines of evidence have indicated that cucurbitacin-I promotes cell cycle arrest and/or apoptosis in glioma, 48,49 lung, 42,50 breast, 51 and other malignancies. [52][53][54][55] Previously we observed that blockade of the JAK/STAT pathway by cucurbitacin-I enhanced the efficacy of SRC family kinase (SFK) inhibition with dasatinib in glioma cells.…”
Section: Introductionmentioning
confidence: 99%